Perlindungan Hukum Terhadap Tenaga Kerja Lokal dalam Undang-undang Nomor 11 Tahun 2020 tentang Omnibus Law Cipta Kerja - May Linda Iswaningsih; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2021)
Regulatory problems and the disharmony of laws and regulations in labor law in Indonesia have forced the government to reform the rules through the omnibus law which aims to reduce the unemployment rate in Indonesia. The concept of a state of law (rechtsstaat) adopted by the Indonesian state includes the protection of human rights as well as legal certainty and is based on the law. Economic development is very important for improving people's welfare. The purpose of this study is to analyze the regulation of the omnibus law of work copyright for local workers in foreign investment companies in Indonesia and the form of legal protection of the omnibus law of work copyright for workers. The type of research used is the type of normative law research with a statutory approach and a conceptual approach. The legal materials used are primary, secondary, and tertiary. The technique of collecting legal materials by analyzing and citing applicable laws and regulations from books, literature, and other sources. The results of the study reveal that the omnibus law concept is one of the breakthroughs to reorganize current regulations. To minimize the occurrence of disharmony and overlapping of existing laws and regulations, the omnibus law is a good plan for structuring regulations. The Indonesian people must formulate new policies that are able to make Indonesia compete with countries in the world to attract investment. These policies must be able to restore the wheels of the slumped Indonesian economy. Regulatory reform is expected to help ensure that laws and regulations in all areas of activity are fully responsive to changing economic, social and technological conditions that surround them.